Życie to droga, czyli "którędy do Ciebie" - Kowalewska-Dąbrowska, Jolanta (Stylistyka, 2021)
The aim of the article is to present comparatively the fragment of view of the world (connected with concept of life) in the Polish language and in the idiolect of Jan Twardowski's poetry. The interpretations are based on Langacker's network model, on Lakoff and Johnson's cognitive model ofmetaphors and on the proposals of Polish authors about using cognitive methods in interpretation of poetry. The conceptualization of life (connected with the conceptua lization of death) can be described both as commonplace (gr. topós coinós) - life is road, and as cognitive metaphor: LIFE IS ROAD / JOURNEY. The paper presents different particular realizations of this metaphor in the Polish language and in the Tw ardow ski's poetry. The analyses are carried out with the use of profiling method. The most characteristic for Tw ardowski's idiolect is the religious profile of life, conceptualized as a road Uourney) to Heaven (God). So, the religious profi le is the kind of metaphor LIFE IS ROAD I JOURNEY TO HEAVEN / GOD. This profi le is often connected with the profile of heaven. The analysis presented in the article shows that in Tw ardowski's poetic language, otherw ise than in the everyday use of Polish language, a life which is hard and dangerous (as a road to God) is more valuable than a life which is easy and simple.